THE IMPACT OF PULSES' PHYTOCHEMICALS AND BIOACTIVE COMPOUNDS ON HEALTH - A. Meharajbegum, Vikas K. Anakal, G. Jahirhussain, M. I. Niyas Ahamed, C. Kiruba Rani, N. Pragathi, (Chelonian Research Foundation, 2023)
During its sixty-eighth session on December 20, 2013, the United Nations General Assembly declared that 2016 would be recognized as the International Year of Pulses (IYP). The Food and Agriculture Organization (FAO) of the United Nations was designated to oversee the implementation of the International Year, in partnership with governments and various organizations. Pulses are a significant reservoir of various phytochemicals and natural bioactive components that are essential for maintaining good health. These grains are highly nutritious, including abundant amounts of protein, complex carbohydrates, soluble dietary fiber, and may be kept for extended periods without any significant loss in their nutritional content. In addition, pulses possess nitrogen-fixing capabilities that enhance soil fertility and exert positive effects on the ecosystem. However, their advantages are frequently undervalued. This mini-review provides a concise overview of the health advantages associated with phytochemicals and bioactive components found in pulses. Keywords: Protein, complex carbohydrates, soluble dietary fiber